The Pedagogy of the Shells: Chiapas and the Rebel Education Zapatista System of National Liberation - Obando Arias, Milagro (2013)
This article describes the premises that currently make up the educational system that has been developed since 1996 in the autonomous indigenous Zapatista communities from Chiapas in the Mexican SouthWest. As a curricular proposal, the “Sistema Educativo Rebelde Zapatista” in Chiapas responds to a specific civil society project and to a specific vision of the human being. To find these tenets, it is necessary to examine the movements that have been developed during twenty years of struggle, actions, and transformations in this society, a society that has declared itself autonomous from the federal government of Mexico. The pedagogical importance of analyzing this type of experiences lies in the possibility of building educational proposals from and for our geopolitical reality. Likewise, it is necessary to know alternative and diverse pedagogies from a critical standpoint.